PERAN SUPPLY CHAIN MANAGEMENT TERHADAP CUSTOMER RETENTION PADA PT. KIMIA FARMA, TBK. - Devina Wistiasari; Golan Hasan; Kelfi Yanti Limanda; Nida Ohanna; Shevia Shevia; Giorgyna Giorgyna (Departemen Manajemen, 2023)
The Covid-19 pandemic has had a broad impact on daily life around the world, including in Indonesia. To gain a competitive advantage, companies must prioritize supply chain management to ensure timely and effective delivery of goods. Equally important to supply chain management is the need for companies to maintain customer retention. Both of these can be achieved with the help of good operational management. In this article, the author uses a qualitative descriptive research method by outlining a systematic approach to writing about operational management, which involves observing manufacturing companies affected by the pandemic and connecting that data to supply chain management and customer retention. The purpose of this article is to investigate how companies in the pharmaceutical industry, particularly PT Kimia Farma, Tbk, have dealt with issues before, during, and after the pandemic. Through this analysis, it was found that supply chain management is carried out by ensuring the availability of quality health and pharmaceutical products and implementing effective inventory management practices, while to retain customers, companies must focus on improving services and launching digital applications in response to digitization. Successful supply chain management and customer retention strategies are crucial for companies to maintain their existence, both before, during, and after surviving the Covid-19 pandemic.